Family Burden and Parental Distress Following Mild Traumatic Brain Injury in Children and its Relationship to Post-concussive Symptoms - Ganesalingam, Kalaichelvi (2008)
OBJECTIVE: To examine the relationship of mild traumatic brain injuries (TBI) and post-concussive symptoms (PCS) to post injury family burden and parental distress, using data from a prospective, longitudinal study. METHODS: Participants included 71 children with mild TBI with loss of consciousness (LOC), 110 with mild TBI without LOC, and 97 controls with orthopedic injuries not involving the head (OI), and their parents. Shortly after injury, parents and children completed a PCS interview and questionnaire, and parents rated premorbid family functioning. Parents also rated family burden and parental distress shortly after injury and at 3 months post injury. RESULTS: Mild TBI with LOC was associated with greater family burden at 3 months than OI, independent of socioeconomic status and premorbid family functioning. Higher PCS shortly after injury was related to higher ratings of family burden and distress at 3 months. CONCLUSIONS: Mild TBI are associated with family burden and distress more than mild injuries not involving the head, although PCS may influence post injury family burden and distress more than the injury per se. Clinical implications of the current findings are noted in the Discussion section.